(untitled) (Scientific journal of the Fergana State University, 2023)
It is known that in order to turn historical truth into artistic reality, a writer requires a lot of creative research, careful study of the fabric and actual materials. the concept of pathos, which creates and coordinates the poetic idea, becomes clear. Indeed, as a result of many years of creative search, the tetralogy of Muhammad Ali "Great power", which came to the world, is a typical example of this process. Artistic pathos is part of the artistic style. It displays the lyrical and romantic mood. Creative ideas and ideas of the writer are inextricably linked with Pathos. It is theoretically proved that this aspect is related to the meaningful field of tetralogy.